A comparative Study of the Evolution Different Mobile Generations for Wireless Communication (Journal of the College of Basic Education, 2022)
The mobile communication system has revolutionized human life and made the world a small village through communications and data transmission in the form of voice calls, messages or videos with very high download speeds. This paper discusses the different communication technologies for mobile phone generations, starting from the first generation of primitive to the second and third generation, in terms of mobile voice technologies, then the fourth generation as signs of rapid data download speed started, as the speed of connection to the fourth generation networks is ten times higher than the generation connection The third, which led to the improvement of data traffic in the communications network, the high mobility recipe for people who make calls, in addition to improving global system management and improving voice quality, then the great revolution in the fifth generation that is characterized by covering all geographical areas with an increase in the high-frequency spectrum, which is characterized at high frequencies starting from 6 GHz to 100 GHz, in addition to comparing all these generations through illustrative tables.